Contemporary Latin American social and political thought : an anthology - Márquez, Iván, 1965- (Latin American perspectives in the classroom., 2008)
This anthology offers the first serious, broad-ranging collection of English translations of significant Latin American contributions to social and political thought spanning the last forty years. Iván Márquez has judiciously selected narratives of resistance and liberation; ground-breaking texts in Latin American fields of inquiry such as liberation theology, philosophy, pedagogy, and dependency theory; and important readings in guerrilla revolution, socialist utopia, and post-Cold War thought, especially in the realms of democracy and civil society, alternatives to neoliberalism, and nationalism in the context of globalization. Highlighting the vitality, diversity, and originality of Latin American thought, this anthology will be invaluable for students and scholars across the social sciences and humanities.